Are Public Repository Requirements Exacerbating Lack of Diversity?. Issue 6 (June 2020) - May, Thomas
Abstract : Although public repository requirements are aimed at researchers and designed to ensure that the utility of the limited data we have is optimized, these policies also have ramifications for research participants. In this opinion article, I discuss how the nature of such repositories can subject participants whose data are 'banked' to unwitting participation in scientific projects they might find objectionable. In addition, concerns about the privacy of banked genomic data are exacerbated by recent projects that demonstrate the ability to re-identify genomic data, raising the specter of discriminatory or oppressive use of this information. These concerns are most likely to discourage participation in research that requires data sharing among those who have experienced these phenomena and are less likely to discount their likelihood. Highlights: Data sharing subjects participants to unwitting participation in scientific projects they might potentially find objectionable. Concerns about use or misuse of 'banked' genomic data are exacerbated by recent projects that demonstrate the ability to re-identify genomic data. Concerns about potential oppression or discrimination are more likely to discourage participation among those populations who have experienced these phenomena.